Trace gas (CH4, N2O, H2S) distribution in the water column of inland lakes in Poland - Woszczyk, Michał; Majewski, Mikołaj; Schubert, Carsten J.; van Geldern, Robert (Scientific Data, 2026)
We present a data set of trace gas (TG; CH4, N2O and H2S) concentrations and associated hydrochemical parameters (temperature, EC, pH, ORP, TOC, DOC, HCO3-, Cl-, SO42−, NO3-, δ13CDIC) in the water columns of Polish inland freshwater lakes. This data set acts as the first comprehensive source of information on the distribution of TG in lakes of central-eastern Europe. Despite the fact that this region displays relatively high limnicity, it is considerably understudied with regard to the occurrence of TG in lakes. This data set was created to fulfill this gap in biogeochemical knowledge and to provide data which can improve assessing and modelling of TG emissions from aquatic systems. The observations were collected monthly between July 2019 and September 2022 from different water depths in representative sites of three lakes in central (L. Łódzko-Dymaczewskie and L. Dębno) and western (L. Trześniowskie) Poland. The lakes showed different trophic conditions, depths as well as catchment characteristics. The database involves 358 records of CH4/N2O and 507 values of H2S.
CRIS-Team Scopus Importer:2026-02-06